The timbre composition of Claude Debussy’s “Prélude à l’Après-midi d’un faune”: stylistic aspect - Zharkov, Oleksandr; Kokhanyk, Iryna (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2022)
Relevance of the study. In the 20th–21st centuries art music the timbre component determines the processes of form creating, features of composition and dramaturgy, and becomes an essential component of a composer’s individual style system. This makes it necessary to distinguish and to define the concept of timbre composition, to study its functions in forming the text of a music work. The purpose of the article is to study the timbre composition of “Prélude à l’Après-midi d’un faune” by Claude Debussy in the aspect of the composer’s individual style. Methods. The methods of system and functional analysis are used, as well as the stylistic method, which gives possibility to determine the specific features of the timbre composition in the work. The results and conclusions. The analysis of Debussy’s “Prélude à l’Après-midi d’un faune” score proves that the timbre composition clarifies the composer’s intention. The logic of the orchestral timbres changes is aimed at embodying the concept of dissolution, a gradual departure from the subjective through the dramaturgic idea of abandoning timbre solos (pure timbres), from the coloristics of one color to the diversity of all colors and shades, through the movement from pure timbre to doublings and mixes. The uniqueness of the composer’s timbre strategy is the chain of solos (flute — oboe — clarinet — violin — flute), which provides a colorful timbre development of the theme and the entire themes of the piece. At the same time, the timbre composition deepens the three-part structure of the work. It is the timbre design that strengthens the gestural affinity of the themes and the gestural connections between the sections of the work. The study of the text confirms that the timbre composition–its exquisite structure, multilevel symmetry and perfection of proportions–reflects the main features of Debussy’s composing style. Even today, this work remains a source of inspiration for musicians of the 20th–21st centuries, who develop the timbral possibilities of sound, coloristic sound, and constructivism in the creating of music form. The experience of analyzing the timbre composition of “Prélude à l’Après-midi d’un faune” can be useful when studying modern art music works.